Application of ozone and plasmapheresis in complex treatment of uveitis - A. D. Chernyshyova (Бюллетень сибирской медицины)
A new method of treatment of endogenous uveitis have been developed. The method is based on the application of metabolic plasmapheresis with ozonization of cellular weight. Comparative analysis of the treatment results of three groups of 179 patients (209 eyes) has revealed significant superiority of original modification of plasmapheresis. The effect of the presented method of treatment, in authors’ opinion, is caused by immunomodulating effect of plasmapheresis and ozonotherapy, bactericidal and antiviral effects of ozonotherapy. The paper also presents some sanogenetic mechanisms of a new method of treatment – a liquidation of T-cellular immunodeficiency, a decrease of level of circulating immune complexes and some others.